The Gut Microbiota: Emerging Evidence in Autoimmune Diseases. Issue 9 (September 2020) - Zhang, Xuan; Chen, Bei-di; Zhao, Li-dan; Li, Hao
Abstract : The pathogenesis of autoimmune diseases (AIDs) is not only attributed to genetic susceptibilities but also environmental factors, among which, disturbed gut microbiota has attracted increasing attention. Compositional and functional changes of gut microbiota have been reported in various AIDs, and increasing evidence suggests that disturbed gut microbiota contributes to their immunopathogenesis. The accepted mechanisms include abnormal microbial translocation, molecular mimicry, and dysregulation of both local and systemic immunity. Studies have also suggested microbiota-based classification models and therapeutic interventions for patients with AIDs. Further in-depth mechanistic studies on microbiota–autoimmunity interplay in AIDs are urgently needed and underway to explore novel and precise diagnostic biomarkers and develop disease and patient-tailored therapeutic strategies. Highlights: The compositional and functional changes of gut microbiota have been implicated in various autoimmune diseases (AIDs) by high-throughput techniques such as metagenomic sequencing. Correlation studies in humans and interventional studies in animal models have suggested that disturbed gut microbiota is involved in the immunopathogenesis of AIDs. The mechanisms of disturbed gut microbiota include abnormal microbial translocation, molecular mimicry, and dysregulation of both local and systemic immunity. In-depth deciphering of gut microbiota will help us to develop new microbiota-based assessments and interventions for patients with AIDs, which can help with their diagnosis, prognosis and treatment.